An Abbreviated Annotated Bibliography: H. Igor Ansoff - Cowan, Roberta (Routledge, 2007)
Two bibliographies of works of H. Igor Ansoff have appeared in print (Ansoff 1992; Hussey 1999). The latter bibliography attempted to provide additional information to some entries from the former and did not include other entries, without explanation of their omission. The items below may not represent a complete reconstruction of the literature published by Igor Ansoff since much of his work appears to have been in the form of reports and working papers. Henry Mintzberg is reported as having described Ansoff as the 'father of strategic management' (Williams 2002) and stated that 'Igor's real contribution to the literature . . . is not prescriptive but descriptive, in the concepts he provided to us' (Mintzberg 1991: 464). For these reasons it is important to record Ansoff's published works accurately.